Peran Grand Design Pembangunan Kependudukan (GDPK) Pada Fenomena Kependudukan di Indonesia Melalui 5 Pilar Kependudukan - Alfassa, Achmad Isya (LPPM UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2024)
The Grand Design for Population Development is a guideline used to create policies and strategies used for national, provincial and district population development. In the Presidential Decree of the Republic of Indonesia Number 153 of 2014 concerning the Grand Design of Population Development, GDPK consists of 5 pillars which will become a reference document for the implementation of reliable population development. The Grand Design for Population Development consists of 5 pillars of development in the population sector, including Population Quantity Management, Population Quality Improvement, Population Distribution and Mobility Management, Quality Family Development, Population Data and Information Arrangement and Population Administration. It is hoped that the Grand Design Document for Population Development, which consists of 5 pillars, can serve as a guide for the central government and regional governments to overcome population problems and be able to formulate a good and sustainable population policy direction.